Mild and moderate cognitive impairment and mortality among Brazilian older adults in long-term follow-up: The Bambui Health Aging Study - Campos, Cecilia G. (Braz J Psychiatry, 2020)
OBJECTIVE: To compare mortality in older adults with and without mild or moderate cognitive impairment over 15 years of follow-up in a middle-income country, where little information on this subject is available. METHODS: A total of 1,281 community-dwelling older adults were followed-up for a median of 13.3 years. We evaluated their cognitive impairment using the Mini-Mental State Examination, categorizing it as none (1.0 SD above cutoff means), mild (1.0 SD below cutoff means) or moderate (2.0 SD below cutoff means). The date of death was determined by reviewing death certificates. Cox’s proportional hazards models were used to evaluate the risk of mortality in participants with cognitive impairment. RESULTS: Participants with mild or moderate cognitive impairment had a higher mortality risk than those without it in the unadjusted model, but these associations did not remain in the final model. After sex stratification, only men with moderate cognitive impairment had a higher mortality risk in the final model. CONCLUSION: The findings suggest an association between moderate cognitive impairment and all-cause mortality in men in a large Brazilian cohort of older adults.